Written witness testimony - Lach, Rafał (Scientific Journal of Bielsko-Biala School of Finance and Law, 2022)
<span dir="ltr" style="left: calc(var(--scale-factor)*100.94px); top: calc(var(--scale-factor)*226.98px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.05345);" role="presentation">According to Art. 9 sec. 2 of Regulation (EC) No.<span dir="ltr" style="left: calc(var(--scale-factor)*46.80px); top: calc(var(--scale-factor)*237.30px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.984824);" role="presentation">861/2007 of the European Parliament and of the Council of 11 July <span dir="ltr" style="left: calc(var(--scale-factor)*46.80px); top: calc(var(--scale-factor)*247.62px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.998929);" role="presentation">2007 establishing a European Small Claims Procedure, the court <span dir="ltr" style="left: calc(var(--scale-factor)*46.80px); top: calc(var(--scale-factor)*257.94px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.06047);" role="presentation">or tribunal may <span dir="ltr" style="left: calc(var(--scale-factor)*110.30px); top: calc(var(--scale-factor)*257.94px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.985204);" role="presentation">allow written evidence from witnesses, experts or <span dir="ltr" style="left: calc(var(--scale-factor)*46.80px); top: calc(var(--scale-factor)*268.26px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.00477);" role="presentation">parties to be taken. The Regulation applies to cross-<span dir="ltr" style="left: calc(var(--scale-factor)*250.13px); top: calc(var(--scale-factor)*268.26px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.941686);" role="presentation">border cases <span dir="ltr" style="left: calc(var(--scale-factor)*46.80px); top: calc(var(--scale-factor)*278.70px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.00418);" role="presentation">(Regulation of 11 July 2007), <span dir="ltr" style="left: calc(var(--scale-factor)*159.50px); top: calc(var(--scale-factor)*278.70px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.952826);" role="presentation">i.e., <span dir="ltr" style="left: calc(var(--scale-factor)*175.01px); top: calc(var(--scale-factor)*278.70px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.955069);" role="presentation">cases in which at least one of the <span dir="ltr" style="left: calc(var(--scale-factor)*46.80px); top: calc(var(--scale-factor)*289.02px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.997162);" role="presentation">parties is domiciled or habitually resident in a Member State other <span dir="ltr" style="left: calc(var(--scale-factor)*46.80px); top: calc(var(--scale-factor)*299.34px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.994905);" role="presentation">than the Member State of the court or tribunal examining the case <span dir="ltr" style="left: calc(var(--scale-factor)*46.80px); top: calc(var(--scale-factor)*309.66px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.00496);" role="presentation">(Article 3). On the other hand, the Act amending the Act - <span dir="ltr" style="left: calc(var(--scale-factor)*269.45px); top: calc(var(--scale-factor)*309.66px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.964118);" role="presentation">Code of <span dir="ltr" style="left: calc(var(--scale-factor)*46.80px); top: calc(var(--scale-factor)*320.10px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.01842);" role="presentation">Civil Procedure and some other acts of 5 <span dir="ltr" style="left: calc(var(--scale-factor)*212.09px); top: calc(var(--scale-factor)*320.10px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.969362);" role="presentation">December 2008 added <span dir="ltr" style="left: calc(var(--scale-factor)*46.80px); top: calc(var(--scale-factor)*330.42px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.0605);" role="presentation">Art. 505 25<span dir="ltr" style="left: calc(var(--scale-factor)*91.46px); top: calc(var(--scale-factor)*330.42px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.03326);" role="presentation">. Pursuant to § 1 of this provision: The witness sh<span dir="ltr" style="left: calc(var(--scale-factor)*289.39px); top: calc(var(--scale-factor)*330.42px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.13786);" role="presentation">all <span dir="ltr" style="left: calc(var(--scale-factor)*46.80px); top: calc(var(--scale-factor)*340.74px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.06925);" role="presentation">testify in <span dir="ltr" style="left: calc(var(--scale-factor)*83.90px); top: calc(var(--scale-factor)*340.74px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.14594);" role="presentation">writing if <span dir="ltr" style="left: calc(var(--scale-factor)*123.38px); top: calc(var(--scale-factor)*340.74px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.986402);" role="presentation">the court so decides. In this case, the witness <span dir="ltr" style="left: calc(var(--scale-factor)*46.80px); top: calc(var(--scale-factor)*351.06px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.009);" role="presentation">shall make an oath by signing the text of the oath. The witness is <span dir="ltr" style="left: calc(var(--scale-factor)*46.80px); top: calc(var(--scale-factor)*361.52px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.02337);" role="presentation">obliged to submit the text of the testimony to the court within the <span dir="ltr" style="left: calc(var(--scale-factor)*46.80px); top: calc(var(--scale-factor)*371.84px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.01669);" role="presentation">time limit set by the court. The provisions of <span dir="ltr" style="left: calc(var(--scale-factor)*220.85px); top: calc(var(--scale-factor)*371.84px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.999462);" role="presentation">art. 165 § 2, art. 274 <span dir="ltr" style="left: calc(var(--scale-factor)*46.80px); top: calc(var(--scale-factor)*382.16px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.11618);" role="presentation">§ 1 and art. 276 shall apply accordingly. As indicated in the <span dir="ltr" style="left: calc(var(--scale-factor)*46.80px); top: calc(var(--scale-factor)*392.48px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.09893);" role="presentation">justification for the draft of this legal act: Due to the fact that <span dir="ltr" style="left: calc(var(--scale-factor)*46.80px); top: calc(var(--scale-factor)*402.92px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.14999);" role="presentation">Polish law does not know the written form of testifying by <span dir="ltr" style="left: calc(var(--scale-factor)*46.80px); top: calc(var(--scale-factor)*413.24px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.996983);" role="presentation">witnesses and hearing the parties (the excep<span dir="ltr" style="left: calc(var(--scale-factor)*220.49px); top: calc(var(--scale-factor)*413.24px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.03619);" role="presentation">tion applies to mute <span dir="ltr" style="left: calc(var(--scale-factor)*46.80px); top: calc(var(--scale-factor)*423.56px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.03028);" role="presentation">and deaf people, cf. Art. 271 § 2 of the Code of Civil Procedure; <span dir="ltr" style="left: calc(var(--scale-factor)*46.80px); top: calc(var(--scale-factor)*433.88px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.02099);" role="presentation">this provision applies accordingly to hear the parties pursuant to <span dir="ltr" style="left: calc(var(--scale-factor)*46.80px); top: calc(var(--scale-factor)*444.32px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.03109);" role="presentation">the third sentence of Article 304), it was necessary to introduce <span dir="ltr" style="left: calc(var(--scale-factor)*46.80px); top: calc(var(--scale-factor)*454.64px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.01186);" role="presentation">appropriate regulations in this resp<span dir="ltr" style="left: calc(var(--scale-factor)*182.33px); top: calc(var(--scale-factor)*454.64px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.990765);" role="presentation">ect applicable to the European <span dir="ltr" style="left: calc(var(--scale-factor)*46.80px); top: calc(var(--scale-factor)*464.96px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.04155);" role="presentation">Small Claims Procedure.